Fusion of perfusion and diffusion maps with 4D PWI sequences in ischemic stroke lesion outcome prediction - Amorim, Joana Mourão de (2019)
Dissertação de mestrado integrado em Engenharia Biomédica (área de especialização em Eletrónica Médica)